Characterization of humic acids in a continuous-feeding vermicomposting system with horse manure - Hanc, Ales; Enev, Vojtech; Hrebeckova, Tereza; Klucakova, Martina; Pekar, Miloslav (Waste management, 2019)
The increasing numbers of kept horses create problems with processing horse manure as important local waste. This work was focused on horse manure vermicomposting in a real-field continuous-feeding system under controlled conditions, and on the complex study of the maturity and stability of the produced vermicompost. Commonly used simple indicators such as the C/N ratio, N-NH4+/N-NO3- ratio, DOC or ion exchange capacity, and also more advanced spectroscopic and thermoanalytic techniques were used and applied on the humic substances isolated from the vermicompost during its maturation (12 months in total). When compared with the original horse manure, vermicomposting decreased the aliphatic, protein-like, and polysaccharide humic components, whereas vermicomposting increased the aromaticity and contents of oxygen-containing functional groups. The typical tryptophan-like fluorophores in the manure, corresponding to the freshly produced organic matter of biological or microbial origin, were progressively transformed to humic-like fluorophores during vermicomposting. The most thermally labile humic fraction disappeared quickly during the very early vermicomposting stages. The results of spectroscopic and thermogravimetric analyses suggest that stable and mature vermicompost was produced after 6-9 months of vermicomposting, which was also supported by biologically-based maturity indicators.
Keywords: Humic Substances; hnůj; Animals; Horses; huminové látky; Manure; zvířata; Soil; půda; Oligochaeta; koně